ANALISIS PENGARUH PERBANKAN SYARI’AH TERHADAP INDUSTRI KREATIF DI SUMATERA UTARA TAHUN 2006 - 2015 - Andri Soemitra, Erni Yusnita Siregar Saparuddin Siregar (JURNAL EKONOMI DAN BISNIS ISLAM, 2017)
This article aims to determine how much  is the influence the Total Labor, Total Company, Total Export and Total shari?ah Financing, to the GDP of Creative Industries in North Sumatra Indonesia. The research method used is quantitative approach using path analysis with multiple linear regression analysis/ OLS (Ordinary Least Squared). The data used in this research is time series data in the period from 2006 -  2015. The study found that about 76,2% variable Total Labor, Total Company, Total Export and Total shari?ah Financing simultaneously influence the GDP of Creative Industries in North Sumatra in the period 2006 ? 2015, while 23.8% is explained by other factors. Partially the Total Labor, Total Company, Total Export and Total shari?ah Finance, also giving effect to real GDP of Creative Industries in North Sumatra.